Designing Risk-Based Internal Audit Plan in the Internal Auditor Division (A Case Study in PT. XY) - Sudarmono Sudarmono; Agustinus Nicholas L Tobing (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study analyzed the design of a risk-based audit plan in the internal audit division (a case study of PT. XY). It is expected that the implementation of a risk-based audit plan in the internal audit division can support the achievement of the strategic plan of PT. XY. This research used a qualitative method with a descriptive design. The data collection technique was carried out by document analysis and interviews with structured questions, while the analysis technique was conducted with data reduction, data display, and concluding. This study concluded that using the risk-based internal audit plan method yielded several advantages, including more measurable auditable areas aligned with company objectives, number of mandays efficiency, and budget efficiency. Therefore, the authors suggest applying risk-based internal audit (RBIA) in the audit planning process for the following years and performing assurance mapping as a critical factor in supporting the audit planning process.